One-pot synthesis and biological imaging application of an amphiphilic fluorescent copolymer via a combination of RAFT polymerization and Schiff base reaction. Issue 11 (21st March 2015) - Huang, Zengfang; Zhang, Xiqi; Zhang, Xiaoyong; Yang, Bin; Zhang, Yaling; Wang, Ke; Yuan, Jinying; Tao, Lei; Wei, Yen
<x xml:space="preserve">Abstract</x> A novel one-pot strategy for the fabrication of AIE-based FONs was developed via a combination of RAFT polymerization and Schiff base reaction for the first time.